Dynamics Analysis of Globoidal Indexing Cam Mechanism based on Rigid- flexible Coupling Model - Zhang Xingyu; Ge Zhenghao; Li Chengping; Zhang Shuanglin (Jixie chuandong)
Aiming at the globoidal cam indexing mechanism,considering the influence of elastic deformation,bending and twisting factor,combining the knowledge of rigid- flexible coupling dynamics system,a rigid- flexible coupling model of indexing cam mechanism is established by using the Pro / E,ADAMS,ANSYS,and the model is analyzed,a detailed description of the effects of speed,load on the dynamic performance of mechanism is carried out.